2001
DOI: 10.1179/136132801805576743
|View full text |Cite
|
Sign up to set email alerts
|

Voice changes following androgenic hormone treatment in women

Abstract: Androgenic medications have been known to cause changes to the vocal folds and to voice quality for many decades. One such androgen is Danazol, a synthetic derivative of testosterone. Although altered perceptual voice features have been consistently reported following treatment with Danazol, objective measurements of the voice changes have been limited. The current study incorporates a comprehensive assessment battery of vocal function including instrumental techniques, acoustic analysis and perceptual voice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Although caution should be used in comparing non-equivalent studies or extracting data to non-equivalent groups, our results do support previous prospective findings by Nordenskjöld who concluded ‘no significant vocal changes in 23 patients that could be attributed to the androgenic properties of danazol therapy (600 mg/day) at 3 and 6 months’ 6 . Pattie’s subsequent objective study on ten patients treated with danazol found similar results, cautioning against reliance on perceptual descriptions of voice changes 7 .…”
Section: Discussionmentioning
confidence: 88%
“…Although caution should be used in comparing non-equivalent studies or extracting data to non-equivalent groups, our results do support previous prospective findings by Nordenskjöld who concluded ‘no significant vocal changes in 23 patients that could be attributed to the androgenic properties of danazol therapy (600 mg/day) at 3 and 6 months’ 6 . Pattie’s subsequent objective study on ten patients treated with danazol found similar results, cautioning against reliance on perceptual descriptions of voice changes 7 .…”
Section: Discussionmentioning
confidence: 88%